Systematic review of religiosity and social responsibility - Mahmoud Amer (Journal of Business and Socio-Economic Development, 2024)
Purpose – The objective of this study is to establish a link between religiosity and Corporate Social Responsibility (CSR) by conducting a systematic literature review in the field of CSR and religiosity. This will be achieved by screening all available electronic databases. Design/methodology/approach – This paper is a literature review paper using the systematic review – Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, with a practical focus on empirical research to summarize the total effect or outcome of these empirical findings. The methodology includes inclusion and exclusion criteria for the final selection of articles. Findings – In this paper, 31 articles published in well-known CSR journals after the year 2015 were included. The majority of the literature confirms a positive direct/indirect relationship between religiosity and CSR. Research limitations/implications – This paper is limited to the considered databases and the identified searching protocols. Changes in the referred databases or search protocols may affect the results, as results outside these limitations were not considered in this study. Practical implications – This study can serve as a guide for researchers in applying the PRISMA approach. Furthermore, it contributes to the field of religiosity and CSR by offering a comprehensive review of the most recent related publications. Originality/value – This article is unique as it applies the PRISMA framework to conduct the literature review. It is also the first literature study in the field of religiosity and CSR.